Do bank CEOs learn from banking crises? - Yu, Gloria Yang (Journal of Financial Economics, 2025)
Does the early-career exposure of bank CEOs to the 1980s savings and loans (S&L) crisis affect the outcomes of banks they subsequently managed? We measure the S&L crisis exposure by the bank failure rate in the states where CEOs worked during the S&L crisis. Armed with this measure, we find that banks managed by CEOs with higher S&L crisis exposure took on less risk and that these banks better survived the financial crisis of 2008. In particular, CEOs adjusted risk attitudes in areas causing the S&L crisis: their more intense crisis experience reduced banks’ interest rate risk, exposure to risky financial innovation and credit risk. We establish the causal interpretation of the findings by evaluating the impact of crisis exposure via CEO hometown states and exploiting quasi-exogenous turnovers due to CEO retirement. Overall, CEOs learned from the past industry crisis which helped curtail their institutions’ risk exposures and enhance later crisis performance.